How does sex affect the care dependency risk one year after stroke? A study based on claims data from a German health insurance fund. Issue 6 (18th August 2017) - Schnitzer, Susanne; Deutschbein, Johannes; Nolte, Christian H.; Kohler, Martin; Kuhlmey, Adelheid; Schenk, Liane
Abstract: Objectives: The study explores the association between sex and care dependency risk one year after stroke. Methods: The study uses claims data from a German statutory health insurance fund. Patients were included if they received a diagnosis of ischemic or hemorrhagic stroke between 1 January and 31 December 2007 and if they survived for one year after stroke and were not dependent on care before the event ( n  = 1851). Data were collected over a one-year period. Care dependency was defined as needing substantial assistance in activities of daily living for a period of at least six months. Geriatric conditions covered ICD-10 symptom complexes that characterize geriatric patients (e.g. urinary incontinence, cognitive deficits, depression). Multivariate regression analyses were performed. Results: One year after the stroke event, women required nursing care significantly more often than men (31.2% vs. 21.3%; odds ratio for need of assistance: 1.67; 95% CI: 1.36–2.07). Adjusted for age, the odds ratio decreased by 65.7% to 1.23 (n.s.). Adjusted for geriatric conditions, the odds ratio decreased further and did not remain significant (adjusted OR: 1.18 (CI: 0.90–1.53). Discussion: It may be assumed that women have a higher risk of becoming care-dependent after stroke than men because they are older and suffer more often from geriatric conditions such as urinary incontinence at onset of stroke. Preventive strategies should therefore focus on geriatric conditions in order to reduce the post-stroke care dependency risk for women.